Should We Avoid Stupidity in Our Economic Activity? - Kacerauskas, Tomas (Transformations In Business & Economics, 2026)
The paper deals with the different aspects of stupidity in economics. Two theses are developed: stupidity in economic activity manifests itself both negatively and positively, and it is impossible and unnecessary to avoid stupidity in economic activity. The methods of classification, comparison, and philosophical reflection are utilised. The findings indicate that stupidity is inseparable from human activity, which is influenced not only by rational calculations but also by emotions, blind faith, and inadequate assessment of the situation. Its assessment solely from an economic point of view, as causing a loss to oneself and others, limits its interpretation and prevents it from seeing important aspects. Unprofitable activities can be an important lesson to avoid much larger mistakes. Moreover, what seems stupid at a certain time later results to be a wise decision when circumstances and attitudes change.